HISTORY OF SCHOOL, MUSIC EDUCATION (BEFORE 1917) - А. Pekala (Academy of Cognitive and Natural Sciences, 2002)
The article deals with the questions o f formation o f musical upbringing in the history o f Poland before 1917.